Cases of rupture of the diaphragm with atypical radiological signs - Makhambetchin, Murat; Kuraeva, L.; Akberdiev, N. (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Objective: To demonstrate an opportunity of atypical and significance of indirect radiological signs in diagnostics of traumatic rupture of the diaphragm. Methods: We performed a retrospective analysis of case histories and chest X-ray films in 17 patients with disruptions of the diaphragm treated at the Research Institute of Traumatology and Orthopaedics in the period from 2004 to 2013. Results: On the example of two clinical cases it was shown that plain chest radiograph without direct visual displays of the diaphragm rupture makes it possible to identify indirect and even atypical signs of this damage. In particular displacement of the mediastinum to the side of the diaphragm rupture in the first clinical case on the one hand shows a similar atypical picture and on the other one stresses the importance of diagnosing mediastinal shadow position when studied pathology. Atypical displacement of mediastinal shadow toward the diaphragm rupture connected to the combined tense pneumothorax in contralateral hemithorax. If cases of this combination of injuries clear comparison of the results of the initial clinical trial is completely necessary. In the second clinical observation slight decreasing of transparent hemopleura together with a strip of paracostal eclipse is complementary and direct signs of hemothorax. This one coupled with a dislocation of the mediastinum to the healthy side might be an indirect sign of the diaphragm rupture. Conclusions: radiological examination has limited capacities for diagnostics of the diaphragm rupture in case of absence of direct sign (prolaps of organs of the abdominal cavity into the pleural one). However plain radiography of the chest allows to detect atypical and indirect signs of the diaphragm rupture which optimize diagnostics in combination with clinical picture.